Lumbar spine repositioning sense in adolescents with and without non-specific chronic low back pain: An analysis based on sub-classification and spinal regions - Astfalck, R.; O'Sullivan, Peter; Smith, Anne; Straker, Leon; Burnett, A. (Churchill Livingstone, 2013)
Objective: To identify differences in repositioning error in adolescents with and without non-specific chronic low back pain (NSCLBP), sub-groups of NSCLBP and in different spinal regions. Methods: Spinal repositioning error was measured during a seated task. Variables were constant error (CE), absolute error (AE) and variable error (VE) for lower lumbar, upper lumbar and lumbar angles. 28 subjects with NSCLBP were sub-classified using O'Sullivan’s system and compared to 28 healthy controls.Results: Significant differences were noted for AE between adolescents with and without NSCLBP, but no differences were found for CE or VE. When sub-grouped there was a pattern for lower AE and higher VE in the flexion sub-group. This group also displayed a tendency to undershoot the criterion position in the lower lumbar spine. Greater VE was noted in the extension sub-group and those with no NSCLBP in the upper lumbar compared to the lower lumbar spine. Conclusions: Differences in spinal repositioning errors were noted between adolescents with and without NSCLBP and sub-groups of NSCLBP. Those with flexion-pattern NSCLBP had the lowest levels of spinal repositioning ability. Individuals with no-LBP (low-back pain) or extension-pattern NSCLBP displayed greater variability in the upper lumbar spine.